Predicting the emotional labor strategies of Chinese English Foreign Language teachers. (December 2021) - Dewaele, Jean-Marc; Wu, Aihui
Abstract: Teachers routinely make a conscious effort to manage their emotions in front of students. The present study focused on emotional labor strategies from 594 Chinese English Foreign Language (EFL) teachers, seeking to discover which ones are preferred, how they are related to each other and how they are linked to teachers' sociobiographical, institutional, attitudinal, linguistic and psychological characteristics. Statistical analyses revealed that the strategy Expression of naturally felt emotions was preferred to Surface acting and that both dimensions were moderately negatively correlated. Correlation analyses revealed that sociobiographical variables were unrelated to both dependent variables. Multiple regression analyses revealed that the strongest predictors of Expression of naturally felt emotions were attitudes towards students, Emotionality (a factor of Trait Emotional Intelligence) and two institutional variables. Sociability (another factor of Trait Emotional Intelligence) was the only predictor of Surface acting . The findings are linked to previous research and some pedagogical implications are presented. Highlights: Expression of naturally felt emotions (ENFE) is the preferred emotional labor strategy. Attitudes towards students and Emotionality were strong positive predictors of ENFE. Sociability was the only negative predictor of Surface acting.